Jawabanmu

2014-08-24T19:39:35+07:00
A.  -3m + 4n - 6 + 7n - 8m + 10 = -11m + 11n + 4
     -3m + 4n -6 - (7n - 8m + 10) = 5m - 3n - 16
b.  15a + 7b - 5c + (-11a - 12b + 13d) = 4a - 5b -5c + 13d
     15a + 7b - 5c - (-11a - 12b + 13d) = 26a + 19b - 5c - 18d
11 4 11
Jawaban paling cerdas!
2014-08-24T19:46:27+07:00
Penjumlahan .
a. -3m + 4n -6 + 7n - 8m + 10
= -3m - 8m + 4n + 7n -6 + 10
= -11m + 11n + 4
b. 15a + 7b - 5c + (-11a - 12b + 13d)
= 15a - 11a + 7b - 12b - 5c + 13d
= 4a - 5b - 5c + 13d

pengurangan
a. -3m + 4n -6 - 7n - 8m + 10
= -3m - 8m + 4n - 7n -6 + 10
= -11m + 3n + 4
b. 15a + 7b - 5c - ( -11a - 12b + 13d)
= 15a + 7b - 5c + 11a + 12b - 13d
= 15a + 11a + 7b + 12b - 5c - 13d
= 26a + 19b - 5c - 13d
22 4 22